Kinematic and kinetic differences in block and split-stance standing starts during 30 m sprint-running. Issue 8 (14th September 2019) - Macadam, Paul; Nuell, Sergi; Cronin, John B.; Nagahara, Ryu; Uthoff, Aaron M.; Graham, Scott P.; Tinwala, Farhan; Neville, Jono
Abstract: This study aimed to understand the kinematic and kinetic differences between two sprint starts: block and split-stance standing. Fourteen sub-elite male sprinters (100 m time: 11.40 ± 0.39 s) performed block and split-stance standing starts sprints over 30 m of in-ground force platforms in a randomised order. Independent t-tests and repeated measures mixed model analysis of variance were used to analyse the between-condition variables across conditions, and over four step phases. Block start sprints resulted in significantly ( p < .05) faster 5 m (5.0%, effect size [ES] = 0.89) and 10 m (3.5%, ES = 0.82) times, but no significant differences were found at 20 and 30 m. No significant differences were found in any kinematic measure between starting positions. However, block starts resulted in significantly ( p < .001) greater propulsive impulses (6.8%, ES = 1.35) and net anterior-posterior impulses (6.5%, ES = 1.12) during steps 1–4, compared to the standing start. Block starts enable athletes to produce a greater amount of net anterior-posterior impulse during early accelerated sprinting, resulting in faster times up to 10 m. When seeking to improve initial acceleration performance, practitioners may wish to train athletes from a block start to improve horizontal force production.